International student graduation ceremonies: an opportunity for local tourism service providers - Shanka, Tekle; Taylor, Ruth (Routledge, 2003)
This purpose of this paper is to examine the significance of travel when associated with graduation ceremonies for the international student cohort. Due to the global growth in the international student market, the perceived importance of investigating this market in relation to the impact on tourism marketing is of timely significance. A mail survey of international students who completed their studies in a large Western Australian (WA) university in the past few years was conducted in 2001. The aim of the survey was to determine the significance of the following: (a) types of accommodation facilities used by the family/friends when visiting for graduations; (b) the proportion of expenditures on various types of activities; and (c) the differences in spending patterns for various countries of origin; and (d) the overall contribution of visiting friends and relatives (VFR) to the WA tourism sector. Results indicate that at least two to three family members (mostly parents) of graduating international students attend graduation ceremonies in Perth. Results also show that 58% of the visitors use commercial accommodation facilities (mainly hotels/motels) spending $462 on accommodation for staying 5.35 nights on average, and spend $653 on shopping. At least 58% of the graduates returned to Australia since graduation mainly for holidays (54%). Results of the study are discussed and implications for both the tourism and education sectors are highlighted, in addition to future research directions.